Stoic Masculinity in Sisu Movie (2022): A Character and Symbolic Analysis of Main Characters - Prayoga, Kurniawan Agung; Cholifah, Maria; Lutviana, Rizky (UIBU, 2026)
Stoic masculinity emphasizes endurance, emotional control, and rational action and is often represented visually in action movies. This study examines the representation of stoic masculinity in the movie Sisu (2022) through visual and symbolic elements rather than verbal expression. Using a descriptive qualitative method, the data are collected through movie observation and analysis of selected scenes. The analysis applies Roland Barthes’s semiotic theory, focusing on denotative, connotative, and mythic meanings, supported by Stoic philosophy as articulated by Marcus Aurelius. The findings show that stoic masculinity in Sisu is constructed through endurance of physical suffering, emotional control under threat and loss, and rational action in extreme situations. Among the visual symbols identified in the movie, bodily scars and prolonged silence appear as the most dominant signs representing stoic masculinity. Scars function as visual evidence of endurance and survival from past suffering, while silence and minimal speech represent emotional restraint and internal discipline. Other symbolic elements, such as calmness during confrontation, rational responses to injury, and calculated decision making, further reinforce the representation of stoic masculinity.The movie presents stoic masculinity as a visual identity shaped through action, self control, and cinematic techniques, contributing to the understanding of stoic masculinity representation in movie.